Studi Komparatif Terhadap Narasi Eksorsisme Roh Jahat Dalam Film The Nun I Sampai II dan Eksorsisme Yesus Dalam Markus 1:21-28 - Wijaya, Jonathan Cristian; Lo, Lemuel; Wahongan, Jesica (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2024)
Films featuring scenes of the expulsion of evil powers have been widely published to provide entertainment to the public, while also showcasing certain values within the narrative they visualize. One horror genre film that has garnered considerable interest is